Educating society about the unseen, but not unknown, risk factors for severe COVID-19: a step towards overcoming vaccine hesitancy through a more informed public - Kristian M. Hargadon (Inishmore Laser Scientific Publishing Ltd, 2021)
Among the well-documented reasons for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine hesitancy is a lack of perceived threat of COVID-19 illness. Current public health messaging about risk factors for severe COVID-19 supports this misconception, highlighting age and underlying health conditions readily detected in the population as the primary risk factors for COVID-19-associated complications. In addition to these well-publicized risk factors, defects in the type I interferon antiviral defense system have emerged as another significant, though less visible, risk factor for severe COVID-19. Including these findings in public health messaging will promote this knowledge outside of the scientific community and increase awareness that not all COVID-19 risk factors can be readily observed in oneself and others. Efforts to improve public education about these unseen risk factors for severe COVID-19 are likely to influence attitudes towards individual risk of disease complications and may ultimately encourage SARS-CoV-2 vaccine acceptance.